The Kohistan Basic Complex: A Summary based on Recent Petrological Research - Jan, M. Qasim (Journal of Himalayan Earth Sciences, 1977)
The central part of the Kohistan basic complex in the Swat district has been studied in detail petrographically and geochemically. The main rocks of the area -amphibolites, noritic rocks, and quartz diorites-do not appear to be directly related mutually or to the rocks of the Jijal complex (garnet granulites and alpine-type ultramafic rocks). Temperature and pressure estimates suggest that the various metamorphic rocks of the area were formed under different geothermal gradients. It is recommended that the notitic rocks be henceforth called pyroxene granulites.